The Influence of The BBNKB Ii Exemption Policy and The Tax Amnesty Program on Taxpayer Compliance at P3D Iii Samsat Soekarno Hatta, Bandung City - Muhamad Tajiri; Arimbi Triswastika; Muhamad Prakarsa Al Qadr Saleh (Siber Nusantara of Economic and Finance Review, 2026)
The lack of public awareness in fulfilling the obligation to pay vehicle taxes owned can result in various consequences such as arrears and fines due to late payment of vehicle taxes. In response to this situation, the local government provides solutions to overcome the burden on the community. This article aims to determine the effect of the bbnkb II exemption policy and the amnesty program on taxpayer compliance at P3D III Samsat Soekarno Hatta, Bandung City. The type of method applied in this study is a quantitative approach. The data collection technique in this study was carried out through distributing questionnaires to taxpayers as the main respondents at Samsat Soekarno Hatta, Bandung City and observation. All data were processed and analyzed through multiple linear regression methods using SPSS 22. This article found that there was a significant effect of the bbnkb II exemption policy on taxpayer compliance, while there was no effect of the amnesty program on taxpayer compliance. However, when both policies were analyzed simultaneously, a significant effect was found on taxpayer compliance.